2018
DOI: 10.1038/s41419-018-0669-8
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid chemosensitizes breast cancer by triggering ER stress-mediated apoptosis by directly targeting GRP78

Abstract: Stress-induced cellular defense machinery has a critical role in mediating cancer drug resistance, and targeting stress-related signaling has become a novel strategy to improve chemosensitivity. Betulinic acid (BA) is a naturally occurring pentacyclic triterpenoid with potent anticancer bioactivities in multiple malignancies, whereas its underlying mechanisms remain unclear. Here in, we found that BA has synergistic effects with taxol to induce breast cancer cells G2/M checkpoint arrest and apoptosis induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 48 publications
3
61
2
Order By: Relevance
“…Tumor specimens were fixed in 4% paraformaldehyde for 24 h, followed by the protocol as we described previously [17]. Hematoxylin and Eosin staining was conducted using the Hematoxylin and Eosin Staining Kit (Beyotime Biotechnology, Shanghai, China) according to the manufacturer's instructions.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…Tumor specimens were fixed in 4% paraformaldehyde for 24 h, followed by the protocol as we described previously [17]. Hematoxylin and Eosin staining was conducted using the Hematoxylin and Eosin Staining Kit (Beyotime Biotechnology, Shanghai, China) according to the manufacturer's instructions.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…The results of this work showed that BA supplementation reversed the ratios of p-JAK2/JAK2, p-STAT3/STAT3, and Bax/Bcl-2, and reduced the activation of caspase-3, which was confirmed by the TUNEL results; these data suggest that T-2-toxin-induced apoptosis was blocked by BA treatment. Accumulating evidence has demonstrated that BA is able to induce apoptosis in a broad variety of cell types, including human cervical cancer cells, breast cancer cells, and HT-29 colorectal cancer cells [41][42][43]. In our experiment, BA acted as an antiapoptotic agent in the testes of mice treated with T-2 toxin.…”
Section: Discussionmentioning
confidence: 53%
“…Once ER-stress, a large number of unfolded or misfolded proteins will snatch GRP78 that originally binds to three kinds of responsive proteins, making them exposed and activated. At present, it has been found that GRP78 is closely related to the occurrence and development of liver cancer [43], breast cancer [44] and lung cancer [45]. The expression of GRP78 is increased when ER-stress occurs, which can promote the misfolded or unfolded protein to normal status, thereby reducing the endoplasmic reticulum load and maintaining the stability of the intracellular environment.…”
Section: Discussionmentioning
confidence: 99%